Design of active nickel single-atom decorated MoS2 as a pH-universal catalyst for hydrogen evolution reaction. (November 2018) - Wang, Qi; Zhao, Zhi Liang; Dong, Sha; He, Dongsheng; Lawrence, Matthew J.; Han, Shaobo; Cai, Chao; Xiang, Shuhuai; Rodriguez, Paramaconi; Xiang, Bin; Wang, Zhiguo; Liang, Yongye; et al.
Abstract: MoS2 has been considered as a potential alternative to Pt-based catalysts in the hydrogen evolution reaction (HER). However, the presence of the inactive in-plane domains limits their intrinsic electrocatalytic activity of the catalyst. Here, we demonstrate a new approach for activating these inactive sites and therefore dramatically enhancing the activity. We discover that decorating single Ni atom on MoS2 can increase the HER activity in both alkaline and acidic conditions. Experimental and theoretical results indicate that single Ni atom modifiers are inclined to single dispersion in the S-edge sites and H-basal sites of MoS2, resulting in a favorable change in the adsorption behavior of H atoms on their neighboring S atoms and subsequently the HER activity. Consequently, the single-Ni-atom decorated MoS2 (Ni SA -MoS2 ) achieved cathodic current density of 10 mA cm −2 at overpotentials of 98 mV and 110 mV in 1 M KOH and 0.5 M H2 SO4, respectively. The dispersion of the Ni single atoms in the Ni SA -MoS2 is unaffected upon 2000 cycles in both acidic and alkaline conditions. This single atom decorating approach presents a facile and promising pathway for designing active electrocatalysts for energy conversion and storage. Graphical abstract: Ni single atoms anchor on the H-basal site and S-edge site enrich the active sites of MoS2 thus increasing HER activity fx1 Highlights: Cost-effective single Ni atom decorated MoS2 electrocatalysts are synthesized. Ni single atoms can activate the sites at S-edge and basal plane of MoS2. Ni-MoS2 catalysts exhibit superior HER electrocatalytic activities in both acidic and alkaline condition. HER overpotentials of 98 mV and 110 mV were achieved in alkaline and acid condition. Enhanced performance is due to more active Ni sites in MoS2 .